Innocent Victims In The Global War On Terror 2026-02-15T17:04:47+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Salloomi, M. A. (Mohammed A.) (AuthorHouse, 2011)

(untitled)
"The book presents a case that caused abundant arguments between the West & Islam after 09/11/2001. They are the allegations against a lot of the Charity and Humanitarian Organizations which had been accused for supporting Terrorism. Never-the-less [sic] the book replies scientifically to the big question, Does the Islam and it's organizations are new enemies [sic]? Strugglers and wrestler? or competitors. 09/11 had put on the track a new enemy, which led to designation of administrative arrangements, legal measures and political view points that are hardly changeable or can get rid of their legality, even under the changing governmental official-administration. Consequently the unemployment, the poverty and the diseases had increased so much. Most of people and minorities, countries, liberties and the civil rights became innocent victims to an endless war and undetermined delusive enemy and eventually slaughtered the peace-pigeons"--Amazon.com